2005
DOI: 10.1081/clt-200053076
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone Fails to Improve Survival in Amitriptyline-Poisoned Mice

Abstract: Pretreatment with amiodarone does not appear to significantly alter the lethality of amitriptyline poisoning in mice. Given the inability to monitor cardiac activity in this model, further investigation in a larger animal is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…et al found that an i.p. LD 50 dose of amitriptyline was 100 mg/ kg in female Swiss Albino mice (Barrueto et al, 2005). This difference at LD 50 doses of amitriptyline may be explained by the differences in sex and species.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…et al found that an i.p. LD 50 dose of amitriptyline was 100 mg/ kg in female Swiss Albino mice (Barrueto et al, 2005). This difference at LD 50 doses of amitriptyline may be explained by the differences in sex and species.…”
Section: Discussionmentioning
confidence: 85%
“…Three different doses of amitriptyline (125, 100, and 75 mg/kg) were given to 60 mice (n = 20 for each dose, finally n = 60) by i.p. injection (Barrueto et al, 2005). Similarly, the nonlethal dose of selective adenosine A 1 -and A 2areceptor antagonists (i.e., DPCPX and CSC) was confirmed (1, 3, and 5 mg/kg; n = 10 for each dose, n = 30 for each antagonist, finally for two antagonists n = 60) by i.p injection (Prediger and Takahashi, 2005;Bové et al, 2002).…”
Section: Preliminary Studymentioning
confidence: 99%
“…23 The LD50 value for IP administered amitriptyline was used as described in the literature. 21,24 We preferred to deliver the drug IP, based on the fact that this route of administration (IP injection) requires minimal skill and does not result in lesions or signs of pain when drugs are administered. Also, IP injection has the advantage of being both simple and also causes minimum distress to the rats.…”
Section: Discussionmentioning
confidence: 99%
“…Different groups of rats were injected intraperitoneally (IP) with one of the following formulations: (1) amitriptyline-Arena Group S.A., Bucharest, Romania, (n ¼ 18), 100 mg/kg body weight (equivalent for IP lethal dose at 50% [LD50]) 21 in 1 mL NaCl 9% saline vehicle and (2) 1 mL saline for the control group (n ¼ 6).…”
Section: Drugs Administration and Sample Collectionmentioning
confidence: 99%
“…An initial mouse survival study showed that there was no statistical difference in the amitriptyline LD 50 of mice pretreated with amiodarone when compared to a normal saline control [6]. Since hemodynamic monitoring and electrocardiographic (ECG) analysis were not possible in that small-animal model, a swine model was devised to evaluate these critical measures.…”
Section: Effects Of Amiodarone In a Swine Model Of Nortryptiline Toximentioning
confidence: 99%